'A Place of Ideals in Conflict': Images of Antarctica in Australian Literature - Leane, E (Rodopi, 2007)
This chapter examines Australian literature (poetry, fiction, and plays) dealing with Antarctica, focussing on each text's engagement with the Antarctic environment and the debates surrounding it. Beginning with two late nineteenth.century Antarctic utopias, the survey moves through the work of well-known writers such as Douglas Stewart and Thomas Keneally in the mid-century to more recent writing by Dorothy Porter, Les Murray, Caroline Caddy and others. Less familiar material, such as poetry by Antarctic expeditioners themselves, is also discussed. The essay traces a rough progression in Australian representation of the far southern environment, from an initial utopian approach to an emphasis on its stark, 'timeless' icescape as a minimalist backdrop for human dramas to an appreciation of its changeability, complexity, and fragility.